The thermodynamic equations of state (EoS) and processing of polymers - Kowalska, B. (Polimery, 2022)
Thermodynamic EoS of polymers are reviewed and their applications to processing of polymers are presented. Of the theoretical EoS, the Simha-Somcynski equation (cellular model), the Ising equation (crystal lattice model applied to liquid polymers), the Pastine-Warfield equation (liquid polymer chain vibrating in a rigid cylinder), and the Whitaker-Griskey equation (based on the theory of corresponding states) are discussed. Of the empirical EoS, the Spencer-Gilmore and the Tait equations are described, most frequently used in the processing of polymers. EoS applications to injection molding are presented in terms of p-v-T diagrams used to analyze forming cavity processes and injection-compression molding. Possible applications of EoS are explored, intended to describe a large number of polymers differing in property data and aggregation states over broad pressure and temperature ranges. The relationships between EoS and polymer processing fundamentals have so far been little looked into.